28 GHz dual‐layer substrate integrated waveguide slot array antenna combined with quad‐polarization. Issue 10 (29th July 2021) - He, Junling; Yang, Yang; Zhu, Xuyi; Pan, Hui
Abstract: This article presents a compact slot array antenna combined with quad‐polarization for mm‐wave applications. A novel modified short‐circuit termination with inclined slot is proposed in this paper and a dual‐layer structure has been adopted to achieve miniaturization and also to design a circular polarization feeding network. Two linear polarization feeding networks are designed independently so that four polarization states can be realized. Four polarization states, namely vertical linear polarization, horizontal linear polarization, left hand circular polarization (LHCP), and right hand circular polarization (RHCP) can be switched by feeding corresponding ports. Judging from impedance matching and axial ratio (AR), the antenna exhibits wide bandwidth. The −10 dB impedance bandwidth and 3 dB AR bandwidth are better than 14.2% (26‐30 GHz) with gain about 5‐8 dBic for both LHCP and RHCP. The linear polarization states have |S11 | < −10 dB and a gain of 5‐7 dBi over 26.5‐29.5 GHz (10.7%). The size of the slot array antenna is 65 × 65 × 1.156 mm and measured results are consistent with simulations.